2009
DOI: 10.1063/1.3257901
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional null point reconnection regimes

Abstract: Recent advances in theory and computational experiments have shown the need to refine the previous categorisation of magnetic reconnection at three-dimensional null points -points at which the magnetic field vanishes. We propose here a division into three different types, depending on the nature of the flow near the spine and fan of the null. The spine is an isolated field line which approaches the null (or recedes from it), while the fan is a surface of field lines which recede from it (or approach it).So-cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 73 publications
1
143
0
Order By: Relevance
“…The reconnection triggered is different in all three cases. A comprehensive review of three-dimensional null-point reconnection can be found in Priest & Pontin [46] and Pontin et al [47]. Examples of solar scenarios in which reconnection has been triggered at null points by boundary driving include work by Aulanier et al [48], Pariat et al [49], Masson et al [50,51], but these cases are all aimed at modelling coronal mass ejections (CMEs) or explosive events, such as solar flares, rather than studying coronal heating.…”
Section: (A) Behaviour Of Wave Pulses At Topological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconnection triggered is different in all three cases. A comprehensive review of three-dimensional null-point reconnection can be found in Priest & Pontin [46] and Pontin et al [47]. Examples of solar scenarios in which reconnection has been triggered at null points by boundary driving include work by Aulanier et al [48], Pariat et al [49], Masson et al [50,51], but these cases are all aimed at modelling coronal mass ejections (CMEs) or explosive events, such as solar flares, rather than studying coronal heating.…”
Section: (A) Behaviour Of Wave Pulses At Topological Featuresmentioning
confidence: 99%
“…Owing to the additional complexity that the third dimension brings, in three dimensions, the specifics of the boundary perturbation can cause a variety of different current accumulations that are associated with different types of reconnection [46]. In particular, a three-dimensional potential null point's spine is orthogonal to its separatrix surface.…”
Section: (A) Behaviour Of Wave Pulses At Topological Featuresmentioning
confidence: 99%
“…The eigenvalues of the magnetic field gradient B  define whether a null is radial (degenerates into an Xpoint in 2D) or spiral (degenerates into an O-point; Lau & Finn 1990;Parnell et al 1996). In the magnetohydrodynamic (MHD) approximation the theory of magnetic reconnection at null points has been derived by Pontin et al (2004) andPontin & Galsgaard (2007), and reconnection regimes were classified and generalized by Priest & Pontin (2009. Isolated magnetic nulls have been studied by means of MHD ) and kinetic particle-in-cell (PIC; Baumann & Nordlund 2012) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The other 3D null point reconnection regimes developed are the sheared spine/ fan and the torsional spine/fan reconnection regimes. 1,2 In the sheared spine/fan case, generic shearing occurs across either the spine axis, fan plane, or both, resulting in a current sheet at the null point which is localised to either the spine, fan plane, or both depending on the location of the shear. In the torsional spine/fan case, field lines in the vicinity of the fan/spine rotate causing current to become concentrated along the spine/fan.…”
Section: Introductionmentioning
confidence: 99%